2012
DOI: 10.3851/imp2012
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Chemistry of Nucleoside Phosphonate Prodrugs for Antiviral Therapy

Abstract: Considerable attention has been focused on the development of phosphonate-containing drugs for application in many therapeutic areas. However, phosphonate diacids are deprotonated at physiological pH and thus phosphonate-containing drugs are not ideal for oral administration, an extremely desirable requisite for the treatment of chronic diseases. To overcome this limitation several prodrug structures of biologically active phosphonate analogues have been developed. The rationale behind the design of such agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 84 publications
2
76
0
2
Order By: Relevance
“…Thus, these groups facilitate transport across cell membranes and improve the pharmacological properties of the ANPs. 16,17 In agreement with the literature, we have observed that the preparation of various types of prodrugs of the parent ANP-based inhibitors can significantly improve the activity in cell-based antimalarial assays. 13,15 As a prodrug of choice, we have selected compounds with a phosphoramidate linkage 18 having two identical amino acid esters attached, to facilitate entry into the cells.…”
Section: Figsupporting
confidence: 78%
See 1 more Smart Citation
“…Thus, these groups facilitate transport across cell membranes and improve the pharmacological properties of the ANPs. 16,17 In agreement with the literature, we have observed that the preparation of various types of prodrugs of the parent ANP-based inhibitors can significantly improve the activity in cell-based antimalarial assays. 13,15 As a prodrug of choice, we have selected compounds with a phosphoramidate linkage 18 having two identical amino acid esters attached, to facilitate entry into the cells.…”
Section: Figsupporting
confidence: 78%
“…The selection of this particular type of phosphonate prodrug was based on our previous experience which led to an increase of membrane permeability and bioavailability for the antiviral ANPs. 16,18,23,24 In the first step of the one-pot reaction sequence, the cleavage of the phosphonate esters 2 and 3 with Me 3 SiBr in dry pyridine under argon atmosphere forms in situ the corresponding trimethylsilyl esters. In the second step, the reaction of these intermediates with ethyl (or isopropyl for 6j and 7j) (L)-phenylalanine in the presence of 2,2′-dithiodipyridine (Aldrithiol) and triphenylphosphine yielded the corresponding target bisamidates 6a, 6c, 6j and 7a, 7b, 7j and tetra-amidates 8h, 8i and 9h, 9i (Scheme 1).…”
Section: Chemistrymentioning
confidence: 99%
“…However, one of the reasons may be the poor, if any, efficient cellular uptake of the α-CNPs due to their highly charged nature. Cellular uptake should therefore be enhanced by designing lipophilic prodrugs of the α-CNPs neutralizing the phosphonate charge, a strategy that is applied in the clinically used drugs adefovir dipivoxil (Hepsera), tenofovir disoproxil (Viread), and tenofovir alafenamide (36,37). These attempts are currently ongoing in our laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…There are excellent revisions (Bobeck et al, 2010;De Clercq, 2011;Jordheim et al, 2013;Pertusati et al, 2012;Pradere et al, 2014;Sofia, 2011;Zawilska et al, 2013) on this subject that should be consulted for a much more precise and complete information.…”
Section: Introductionmentioning
confidence: 98%
“…Their direct delivery would provide a potential way to circumvent this limitation, but unfortunately these compounds are rapidly hydrolysed by phosphatases. To overcome this drawback, the phosphate group has been replaced with the isoelectric and isosteric phosphonate moiety, providing a chemically and enzymatically more stable derivative that can be also further phosphorylated by nucleotide kinases (Pertusati et al, 2012). For example, Adefovir (Scheme 1) is an acyclic nucleoside phosphonate active against hepatitis B virus and HIV, which exerts its activity by inhibiting the enzyme reverse transcriptase (RT).…”
Section: Introductionmentioning
confidence: 99%